1999
DOI: 10.1016/s1074-7613(00)80040-0
|View full text |Cite
|
Sign up to set email alerts
|

PU.1 and Spi-B Are Required for Normal B Cell Receptor–Mediated Signal Transduction

Abstract: PU.1 and Spi-B have previously been implicated in the regulation of genes encoding B cell receptor (BCR) signaling components. Spi-B-/- B lymphocytes respond poorly to BCR stimulation; PU.1-/- mice, however, lack B cells, precluding an analysis of BCR responses. We now show that PU.1+/- Spi-B-/- B cells exhibit more extensive defects than Spi-B-/- B cells, indicating that both PU.1 and Spi-B are required for normal BCR signaling. Strikingly, BCR cross-linking results in substantially reduced protein tyrosine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(120 citation statements)
references
References 51 publications
3
116
1
Order By: Relevance
“…This notion was supported by data presented by Borràs et al 36 However, other data suggested that both PU.1 and Spi-B upregulate gene expression. 37 To our knowledge, this is the first time that Sp1 has been shown to bind at the À1087 position in the human IL-10 promoter. The results of the EMSAs in the present study indicated that Sp1 has a higher affinity for this site than PU.1 and Spi-B.…”
Section: Sp1 Transcription Factor Binds To the Il-10 à1087 G-allele Lmentioning
confidence: 84%
“…This notion was supported by data presented by Borràs et al 36 However, other data suggested that both PU.1 and Spi-B upregulate gene expression. 37 To our knowledge, this is the first time that Sp1 has been shown to bind at the À1087 position in the human IL-10 promoter. The results of the EMSAs in the present study indicated that Sp1 has a higher affinity for this site than PU.1 and Spi-B.…”
Section: Sp1 Transcription Factor Binds To the Il-10 à1087 G-allele Lmentioning
confidence: 84%
“…PU.1 is expressed in multiple hemopoietic lineages, including all stages of B cell development, while the expression of Spi-B is restricted to B cells and T cells (18 -20). Targeted null mutation of Spi-B does not affect B cell development, but results in defective BCR-mediated responses (21,22). Both PU.1 and Spi-B are expressed in the B cell lineage beginning at the pro-B cell stage and appear to interact with identical DNA binding sites (15).…”
Section: Cells (4)mentioning
confidence: 99%
“…Both PU.1 and Spi-B are expressed in the B cell lineage beginning at the pro-B cell stage and appear to interact with identical DNA binding sites (15). Therefore in developing B cells, the available evidence indicates that PU.1 and Spi-B are functionally interchangeable (22,23).…”
Section: Cells (4)mentioning
confidence: 99%
“…The absence of PU.1 during embryogenesis results in delayed development and reduced numbers of T cells, likely due to the ine cient commitment and/or early di erentiation of T-cell progenitors Spain et al, 1999). Without PU.1, B cells demonstrate marked abnormalities in their B cell mediated signal transduction (Garrett-Sinha et al, 1999). Additionally, terminally di erentiated B cells appear to be absent in PU.1 knockout mice .…”
Section: Ets Transcription Factors In Hematopoiesis Vasculogenesis Amentioning
confidence: 99%